Effect of aerobic capacity and heart's ability after two years swimming training in adoloscent athletes - Enqian, R. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study is to investigate the effects on anaerobic threshold, maximal aerobic power (VO2max) and heart's ability of adolescent athletes after two years swimming training, the changeable extent through training as well as the relationship between the increase of aerobic capacity and the change of heart's ability.